2017
DOI: 10.1021/acs.energyfuels.7b00882
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Chemical Structures of Compounds in Crude Oil Based on the Tandem Mass Spectra of Standard Compounds Obtained at the Same Normalized Collision Energy

Abstract: In this study, the tandem mass spectra of 25 standard compounds, obtained at a normalized collision energy of 50, were used to investigate the structures of crude oil. The product ion distributions of these standard compounds were dependent on the number and length of their alkyl side chains. Long alkyl side chains (C n H2n , n ≥ 5) were easily lost during molecular collision, leaving behind methyl groups on the aromatic cores. In contrast, compounds with short interlinking alkyl chains (C n H2n , n ≤ 1) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Tandem MS is the most widely used technique for examining the chemical structures of analytes in various types of organic mixtures (Capley et al, 2010;Ha et al, 2017;Osterholz et al, 2015;Reemtsma et al, 2008;Stenson et al, 2003;Witt et al, 2009;Zark et al, 2017). A neutral CO 2 loss is commonly observed in the tandem MS data of EOM.…”
Section: Structural Motifs Analyzed Using Msmentioning
confidence: 99%
“…Tandem MS is the most widely used technique for examining the chemical structures of analytes in various types of organic mixtures (Capley et al, 2010;Ha et al, 2017;Osterholz et al, 2015;Reemtsma et al, 2008;Stenson et al, 2003;Witt et al, 2009;Zark et al, 2017). A neutral CO 2 loss is commonly observed in the tandem MS data of EOM.…”
Section: Structural Motifs Analyzed Using Msmentioning
confidence: 99%
“…The chromatographic separation was improved by using SFC (Figure S7, supporting information), and the SFC peak at 8.2 min was determined to correspond to the peak at 18.7 min detected by HPLC/Orbitrap HRMS, based on the consistency of this ion being detected in the OSPW‐A, OSPW‐B‐1, GW‐2C and GW‐DP5 samples, and being absent in the method blank, BG‐3 and BG‐6 samples. SFC/Orbitrap MS/MS analysis was performed on the m/z 213.1644 ion at 8.2 min, and the spectrum showed a series of product ions separated by 14 m/z units (CH 2 ) indicative of a linear alkyl chain 53 . The double‐bond equivalent number (DBE = 7) of this entity (C 16 H 20 ) indicated the probable existence of a naphthalene structure.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, loss of an ethyl or propyl group will yield two fragment ions separated by the mass of CH 2 . Previous studies have demonstrated that the fragmentation pattern can be used to elucidate the core structures of crude oil compounds. …”
Section: Resultsmentioning
confidence: 99%
“…Tandem mass spectrometry with collision-induced dissociation (CID) or infrared multiphoton dissociation coupled with UHR-MS has been used to study fragmentation patterns of crude oil compounds. For example, CID was used to elucidate the maximum number of carbons in the alkyl chains and chemical structures of compounds in chromatographically simplified vacuum gas oil . The fragmentation patterns helped to understand core structures of oil compounds. , …”
mentioning
confidence: 99%